Foreword: Equality, the Elusive Value - Robert G. Dixon Jr. (Washington University Law Quarterly, 1979)
In America there has been a special tension, indeed a tragic tension not resolved, between the ideals of equality of opportunity and individualism and the reality of black slavery and its aftermath.
Keywords: Equality